Державна політика у сфері теплозабезпечення на базі НВДЕ (Економічні інновації, 2012)
В статті розглянута нормативно-законодавча база України та механізми управління ефективним розвитком теплозабезпечення на базі НВДЕ. Considered normative and legislative base of Ukraine and mechanisms for managing the development of effective heating based on alternative renewable energy sources.